The vertices of a rectangle are Q (2, -3), R (2,4), S (5,4), and T (5, -3).

4. Translate rectangle QRST 3 units left and 3 units down to produce rectangle Q'R'S'T'. Find the area of QRST and the area of rectangle Q'R'S'T'.


5. Compare the areas. Make a conjecture about the areas of a preimage and its image after a
translation.


6. The vector PQ=(4,1) describes the translation of A (-1, w) onto A' (2x+1, 4) and B (8y-1,
1) onto B' (3,32). Find the values of w, x, y, and z.

The vertices of a rectangle are Q 2 3 R 24 S 54 and T 5 3 4 Translate rectangle QRST 3 units left and 3 units down to produce rectangle QRST Find the area of QR class=

Respuesta :

4) [tex]A_{QRST} = A_{Q'R'S'T'} = 9[/tex].

5) The areas of the rectangles QRST and Q'R'S'T' are the same since the translation of the geometric loci conserved the Euclidean distance.

6) x = 1, w = 3, y = - 1/4, z = 1/3

How to analyze and apply rigid transformations

Rigid transformations are transformations applied on geometric loci such that Euclidean distance is conserved. In this question we have applications of translations, a kind of rigid transformation.

Exercise 4

In this part we must determine the areas of rectangles QRST and Q'R'S'T':

Rectangle QRST

A = RS · QT

A = 3 · 3

A = 9

Rectangle Q'R'S'T'

Q'(x, y) = (2, - 3) + (- 3, - 3)

Q'(x, y) = (- 1, - 6)

R'(x, y) = (2, 4) + (- 3, - 3)

R'(x, y) = (- 1, 1)

S'(x, y) = (5, 4) + (- 3, - 3)

S'(x, y) = (2, 1)

T'(x, y) = (5, - 3) + (- 3, - 3)

T'(x, y) = (2, - 6)

A = R'S' · Q'T'

A = 3 · 3

A = 9

The rectangles QRST and Q'R'S'T' have both an area of 9 square units.

Exercise 5

The areas of the rectangles QRST and Q'R'S'T' are the same since the translation of the geometric loci conserved the Euclidean distance.

Exercise 6

In this case, we must solve the following equations:

PQ = A'(x, y) - A(x, y)

(4, 1) = (2 · x + 1, 4) - (- 1, w)

(4, 1) = (2 · x + 2, 4 - w)

(4, 1) = (2 · x, - w) + (2, 4)

(2, - 3) = (2 · x, - w)

(x, w) = (1, 3)

PQ = B'(x, y) - B(x, y)

(4, 1) = (3, 3 · z) - (8 · y - 1, 1)

(4, 1) = (2 - 8 · y, 3 · z)

(4, 1) = (- 8 · y, 3 · z) + (2, 0)

(2, 1) = (- 8 · y, 3 · z)

(y, z) = (- 1/4, 1/3)

To learn more on translations: https://brainly.com/question/17485121

#SPJ1